Ectodomain shedding by ADAM17 (a disintegrin and metalloproteinase 17) in canine neutrophils - Snyder, Kristin M. (Vet Immunol Immunopathol, 2020)
ADAM17 is a transmembrane protease expressed by most cells in humans and mice that cleaves cell surface substrates primarily in a cis manner, a process referred to as ectodomain shedding. ADAM17 has numerous substrates and plays a broad role in various physiological processes, including as a key regulator of inflammation. At this time, little is known about ADAM17 expression and function in dogs. A well-established ADAM17 substrate is the leukocyte adhesion protein CD62L (L-selectin). We show that a selective inhibitor of ADAM17, but not an inhibitor of its most closely related family member ADAM10, blocks CD62L shedding upon canine neutrophil activation. We also tested several anti-human ADAM17 monoclonal antibodies (mAbs) for staining canine neutrophils. Although most did not recognize canine neutrophils, the mAbs MEDI3622 and D1(A12) did. They also blocked the downregulation of CD62L upon neutrophil activation. MEDI3622 is a human IgG antibody and we found that a canine chimeric version of this mAb also blocked CD62L shedding by canine leukocytes. Taken together, our findings provide the first direct evidence of ADAM17 expression and sheddase activity in dogs, establishing a potential therapeutic target for various inflammatory disorders.